Infantile fibrosarcoma with a novel RAF1 rearrangement: The contemporary challenge of reconciling classic morphology with novel molecular genetics - Cheryl M. Coffin; Carol Beadling; Tanaya Neff; Christopher L. Corless; Jessica L. Davis (Elsevier, 2020)
Since the discovery of the ETV6-NTRK3 gene fusion in infantile fibrosarcoma two decades ago, it has become an important diagnostic marker because it is found in the majority of cases. However, the development of new molecular tests, including next generation sequencing, has uncovered additional gene fusions and other oncogenic mutations in tumors with the clinical and morphologic features of infantile fibrosarcoma. We present a case of infantile fibrosarcoma harboring a novel BMPR1A-RAF1 fusion and having a favorable outcome 6 years after surgery. This new structural alteration adds to the list of genetic aberrations in infantile fibrosarcoma and provides another example of the challenge of reconciling classic morphology with novel molecular genetics.